2017
DOI: 10.1002/elsc.201600232
|View full text |Cite
|
Sign up to set email alerts
|

Engineering bi‐functional enzyme complex of formate dehydrogenase and leucine dehydrogenase by peptide linker mediated fusion for accelerating cofactor regeneration

Abstract: This study reports the application of peptide linker in the construction of bi‐functional formate dehydrogenase (FDH) and leucine dehydrogenase (LeuDH) enzymatic complex for efficient cofactor regeneration and L‐tert leucine (L‐tle) biotransformation. Seven FDH‐LeuDH fusion enzymes with different peptide linker were successfully developed and displayed both parental enzyme activities. The incorporation order of FDH and LeuDH was investigated by predicting three‐dimensional structures of LeuDH‐FDH and FDH‐LeuDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 50 publications
(65 reference statements)
1
40
0
1
Order By: Relevance
“…Some studies point out that by performing computational simulations and/or using linker databases, a more consistent and less arbitrary design can be established, as exemplified by the studies mentioned above, even though up to now this has hardly been integrated with enzyme fusions. In one study, simulations were used to decide the gene order for a fusion enzyme of formate dehydrogenase with leucine dehydrogenase …”
Section: Fusion Design and Linker Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies point out that by performing computational simulations and/or using linker databases, a more consistent and less arbitrary design can be established, as exemplified by the studies mentioned above, even though up to now this has hardly been integrated with enzyme fusions. In one study, simulations were used to decide the gene order for a fusion enzyme of formate dehydrogenase with leucine dehydrogenase …”
Section: Fusion Design and Linker Designmentioning
confidence: 99%
“…By combining enzymes in this fashion, a single multifunctional biocatalyst can be produced that can catalyze a cascade of reactions. Remarkably, in a number of studies, evidence was found that the covalently tethered enzymes outperform the classic combination of the separate enzymes in some features such as enhanced expression, higher conversions of a cascade reaction, improved stability,, and improved catalytic activity . However, these promising observations are not consistent across studies, and generic methods to predictably design an effective bifunctional biocatalyst are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…(rigid or flexible) (Lu and Feng, 2008;Chen et al, 2012) and fusion orientation (forward or reverse) (Zhang et al, 2017) could significantly affect the performance of fusion proteins. Borneman and colleagues (Lee et al, 2016) once pointed out that fusing a coumarate-CoA ligase (4CL) with benzalacetone synthase from Rheum palmatum (RpBAS) in the 4CL-RpBAS orientation gave rise to significant improvement on final raspberry ketone levels, but the reverse version (RpBAS-4CL) did not work.…”
Section: Switch Of the Biosynthesis Pathway To Dhaa By Fusion Proteinsmentioning
confidence: 99%
“…Inspired by sophisticated protein complexes in nature [15,16], arti cial multi-enzyme systems have been reported to improve structural stability, promote the cofactor regeneration e ciency and reduce the cost of free enzyme system [17,18]. LeuDH and FDH with PDZ (PSD95/Dlg1/Zo-1) domain and the corresponding ligand of the metazoan (PDZlig) were fused and assembled as multiple supramolecules to improve the NAD(H) recycling e ciency and structural stability [19]. A series of bifunctional enzyme complexes fusing LeuDH and FDH with different peptide linkers were built [20], which could accelerate the transfer of cofactors to increase catalytic rate and stabilize enzyme structure.…”
Section: Introductionmentioning
confidence: 99%